2004
DOI: 10.1016/s0960-9822(04)00381-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Centromere and Kinetochore ProteinsImplications for Checkpoint Signaling and Silencing

Abstract: A missing component of this model, however, is a set of proteins responsible for the recruitment, production, Introduction and release of a wait signal, i.e., the factors that facilitate the proposed catalysis. One important characteristic of Genomic integrity is maintained by a number of checkcomponents of such a catalytic kinetochore scaffold points that act during each cell cycle. The prevention would be a long residence time at unattached kinetoof gross chromosome missegregation and the resulting chores an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
176
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(193 citation statements)
references
References 1 publication
16
176
1
Order By: Relevance
“…The release of GFP-Mad2 at an early stage of Drosophila NPC disassembly in prophase and the late recruitment of Mad1 and Mad2 at the NE corroborate previous observations in Xenopus and human cells (Chen et al, 1996;Shah et al, 2004). However, we show in addition that relocalization of Drosophila Mad1 and Mad2 to the NE occurs in two steps, with their nuclear import preceding their NE association.…”
Section: Mad1 and Mad2 During Drosophila Mitosissupporting
confidence: 79%
“…The release of GFP-Mad2 at an early stage of Drosophila NPC disassembly in prophase and the late recruitment of Mad1 and Mad2 at the NE corroborate previous observations in Xenopus and human cells (Chen et al, 1996;Shah et al, 2004). However, we show in addition that relocalization of Drosophila Mad1 and Mad2 to the NE occurs in two steps, with their nuclear import preceding their NE association.…”
Section: Mad1 and Mad2 During Drosophila Mitosissupporting
confidence: 79%
“…2) [reviewed in . For example, Bub1p binds to Bub3p throughout the cell cycle [reviewed in [Howell et al, 2000[Howell et al, , 2004Shah et al, 2004]. The association of SAC proteins with kinetochores is important for SAC function [Kadura et al, 2005;Taylor et al, 1998;Vanoosthuyse et al, 2004] perhaps because it alters the binding interactions between SAC proteins and influences the formation of the mitotic checkpoint complex (MCC) [Sudakin et al, 2001], which imposes a cell cycle arrest by binding to the Anaphase Promoting Complex (APC).…”
Section: A Consensus Model For Spindle Checkpoint Functionmentioning
confidence: 99%
“…Fluorescence recovery after photobleaching (FRAP) revealed that there were two pools of Mad2 at kinetochores in mammalian cells: a more resident pool that corresponded to the Mad1-C-Mad2 core complex and a fast-exchanging pool that corresponded to a second Mad2 molecule bound to the Mad1-C-Mad2 core through asymmetric dimerization (32). This second Mad2 molecule is likely in the I-Mad2 conformation because I-Mad2-CMad2 is the most stable asymmetric Mad2 dimer in vitro (24).…”
Section: I-mad2 Formation Facilitates the Spontaneous O-mad2 To C-mad2mentioning
confidence: 99%